Recovery of effective HIV-specific CD4+ T-cell activity following antiretroviral therapy in paediatric infection requires sustained suppression of viraemia. (17th July 2018) - Adland, Emily; Mori, Luisa; Laker, Leana; Csala, Anna; Muenchhoff, Maximilian; Swordy, Alice; Mori, Masa; Matthews, Philippa; Tudor-Williams, Gareth; Jooste, Pieter; Goulder, Philip
Abstract : Background: The success of increasing access to antiretroviral therapy (ART) in paediatric HIV infection prompts the question of the potential for eradication of HIV infection in this age group. 'Shock-and-kill' HIV cure approaches, currently in development, may depend upon an effective antiviral T-cell response to eradicate virus-infected cells. Method: We here investigate the ability of HIV-infected children receiving ART from early childhood (median 24 months' age) to generate effective HIV-specific CD4 + and CD8 + T-cell immune responses that would facilitate future immune-based cure therapies. Results: Initial analysis of ART-naive HIV-infected children demonstrated that maintenance of normal-for-age absolute CD4 + T-cell counts was strongly linked to high IL-2 production and polyfunctional HIV-specific CD4 + T-cell responses ( P  < 0.0001 in each case). Low viral load was, similarly, strongly associated with markedly low IFN-γ and high IL-2 HIV-specific CD4 + T-cell responses ( P  < 0.0001). In children receiving ART, establishment of this immune profile (high IL-2 and low IFN-γ HIV-specific T-cell production) was strongly related to the duration of viraemic suppression. Failure to suppress viraemia on ART, and even the successful suppression of viraemia interrupted by the occurrence of transient viraemia of more than 1000 HIV copies/ml, was associated with an immune profile of high IFN-γ and low IL-2 HIV-specific T-cell responses and low polyfunctionality. Conclusion: These data are consistent with recovery of functional CD4 + T-cell responses in ART-treated children, in contrast to relative lack of CD4 + T-cell function recovery described in ART-treated adults. However, the challenges of achieving long-term suppression of viraemia in ART-treated children through adolescence remain daunting. Abstract : Supplemental Digital Content is available in the text